Pegada hídrica e desempenho econômico da cultura do coentro (Coriandrum sativum L.) no agreste sergipano - Bomfim, José Murilho Farias (2017)
The rationalization of water use in agriculture is not only through the adoption of certain efficient systems, but also through the use of rational strategies that minimize waste and reduce environmental impacts. Another highly limiting aspect is productive efficiency, making it necessary to use production cost estimates in the management of fruit and vegetable companies to provide system information for decision making. The production of irrigated coriander (Coriandrum sativum L.) is an activity characterized by the cost of production per hectare cultivated, in this context the accounting of the water footprint and the economic performance allow the efficient decision making in relation to the water management and the minimization of costs in the sense of Adequately allocate the resources available for the given crop. This work aims to determine the Water Footprints (PH): green, blue and gray culminating with the economic analysis of coriander culture in the Agreste region of the State of Sergipe. The PH analysis was based on data from the tabocas cultivar produced at Hortaliças Vida Verde Company, located in the city of Itabaiana / SE. The data analyzed refer to the years 2013 to 2015 during the winter, spring, summer and fall seasons. For the economic performance, the productivity data for the year 2016 was used as a base, in an area of 900 m2, for which economic indicators such as gross revenue, net revenue and the profit and cost ratio were used. The results obtained indicated values for each season: winter (PHgreen 62%, PHblue 36% and PHgrey 2%); Spring (PHgreen 5%, PHblue 94% and PHgrey 1%) summer (PHgreen 6%, PHblue 93% and PHgrey 1%) and autumn (PHgreen 18%, PHblue 81% and PHgrey 1%) having the average participation of PHblue (81%), followed by PHgreen (17%) and PHgrey (2%) in the contribution of the total water footprint to the irrigated coriander. The highest percentage was obtained from the blue PH corresponding to the intensive use of the irrigation system. While the lower percentage obtained in PH gray corresponded to the low use of synthetic fertilizers. The productivity of the crop presented satisfactory results in the economic indicators. Finishing with the following values: gross revenue of R $ 8,437.50, net revenue of R $ 6,226.78 and cost benefit ratio was R $ 3.82. This means that for each R $ 1.00 (one real) used in the production cost of the crop, there was a return of R $ 3.82. The input that most burdened the cost of production was castor bean cake corresponding to 49% of the other fertilizers. The applications of these indicators in the company will contribute to positive actions to understand the challenges related to water consumption and maximize their profitability in production.